2005
DOI: 10.1159/000088962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mupirocin at Subinhibitory Concentrations on Biofilm Formation in <i>Pseudomonas aeruginosa</i>

Abstract: Background: Subinhibitory concentrations of mupirocin can suppress flagellar formation in Pseudomonas aeruginosa. In this study, we evaluated the effect of mupirocin on biofilm formation in P. aeruginosa. Methods:P. aeruginosa PAO-1 (MIC, >1,024 µg/ml for mupirocin) was used. Viable bacteria adhering or forming biofilm on a Cell Desk were counted and observed by scanning electron microscopy. Results: With or without continuous exposure to 256 µg/ml of mupirocin, counts of adherent and/or biofilm-forming bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…Particularly, there are many reports about the resistances of biofilms of Ps. aeruginosa (Ishikawa & Horii, 2005;Landry, An, Hupp, Singh, & Parsek, 2006), Stap. aureus (Shanks et al, 2005;Valle et al, 2003) and Listeria monocytogenes (Carpentier & Chassaing, 2004;Chemielewski & Frank, 2006) because of their strong resistances against disinfectants and for serious medical reasons, such as nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, there are many reports about the resistances of biofilms of Ps. aeruginosa (Ishikawa & Horii, 2005;Landry, An, Hupp, Singh, & Parsek, 2006), Stap. aureus (Shanks et al, 2005;Valle et al, 2003) and Listeria monocytogenes (Carpentier & Chassaing, 2004;Chemielewski & Frank, 2006) because of their strong resistances against disinfectants and for serious medical reasons, such as nosocomial infections.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally perceived that naturally occurring antibiotics are weapons in intermicrobial competition, and should reduce fitness and virulence of pathogens even at subinhibitory concentrations. Many previous reports support this hypothesis (Carfartan et al, 2004;Fonseca et al, 2004;Wozniak and Keyser 2004;Ishikawa and Horii, 2005), but a few studies have shown that some antibiotics at subinhibitory concentrations can activate the expression of some important virulence genes in Salmonella typhimurium and E. coli (Goh et al, 2002) and enhance biofilm formation (Hoffman et al, 2005). There is evidence suggesting that antibiotics act as signal molecules regulating bacterial gene expression and modulating bacterial fitness (Linares et al, 2006).…”
mentioning
confidence: 98%
“…Subinhibitory concentrations of antibiotics may affect various bacterial virulence factors. They can act on the morphology and the antigenicity of the bacteria (11,12), on the growth of bacteria (13), on the synthesis and secretion of enzymes (14,15) and can act on bacterial adherence (16,17). All these factors contribute to the reduction of bacterial pathogenicity.…”
Section: Discussionmentioning
confidence: 99%